MODEL SIMULASI PENGUJIAN VIGOR DUA VARIETAS KEDELAI PADA KONDISI MEDIA TUMBUH BERSALINITAS TINGGI - Halimursyadah Halimursyadah; Said Imran; Agamna Rahmat (Universitas Teuku Umar, 2018)
This study aims to determine the correlation between viability and vigor test results of laboratory and field conditions of high salinity in two varieties of soybean plants. The research was conducted in January to May 2015. This study consisted of two experiments. The first experiment was conducted at the Laboratory of Science and Technology Seed and second trials in experimental field of the Faculty of Agriculture University of Syiah Kuala. Materials used Anjasmoroand Kipas Merah soybean seed varieties, sea water Alue Naga, distilled water, top soil, and rice paper. The design is completely randomized design in the laboratory and in the field randomized block design. Variables measured in the laboratory is the potential for growth, germination, speed of growth and seedling dry weight of normal, while in the field is a potential to grow, the ability to grow, plant height 15, 30, 45 days after planting (DAP), weight mass wet and weight mass dry 45 DAP. The results showed the relationship between testing in the laboratory and in the field with a correlation coefficient of 0.98. Increased salinity concentration is bad for seed germination and plant growth. Anjasmoro varieties more tolerant to salinity than Kipas Merah at variable of plant height by 15, 30, 45 DAP. Keywords: salinity, variety, viability, vigor